Realizing Architecture’s Disruptive Potential - Shajay Bhooshan (Oz, 2016)
Digital technologies—computers and computer-controlled machines have pervaded all aspects of life, delivering sustained and accelerated rates of societal and economic evo - lution. Yet, in architecture, such an embrace of digital technologies and attendant intellectual disposition is not widely accepted. Whilst increasing numbers of progressive firms and research institutions are forging rapidly forward in such a technological upgrade, the larger populace of architects and the architecture produced thereof is decidedly averse to it.